Opportunities and Challenges of Islamic Law in Indonesia's National Legal System from Constitutional Perspective - Muh. Arifin; Zulfikar Putra; Karman Karman (Program Studi Hukum Tata Negara, 2026)
This research aims to analyse the opportunities and challenges of applying Islamic law from a legal perspective in Indonesia. The background to this study is based on the fact that Islamic law has played a significant historical and normative role in the formation of the legal system in Indonesia. However, in practice, there are complex dynamics involved in integrating the principles of Islamic law into the pluralistic national legal framework. The results of the study indicate that there is significant potential for Islamic law to contribute to the strengthening of morality and justice within the national legal system. This potential is reinforced by the presence of Islamic law within the Indonesian legal system through regulations such as the Compilation of Islamic Law and the recognition of Sharia Courts in certain regions. This research employs a qualitative an empirical legal approach that analyzes legal phenomena occurring in society. Data were obtained through a review of the literature on regulations, legal doctrines, judicial decisions, and previous research relevant to this topic. The conclusion is that Islamic law has great potential to contribute to Indonesia’s national legal system. One of the key opportunities lies in public acceptance of the principles of Islamic law, particularly in private law areas such as marriage, inheritance and Islamic finance. Regulations such as the Compilation of Islamic Law and the existence of institutions such as the Sharia Court in Aceh serve as concrete examples that Islamic law can be applied within the national legal framework with strong normative support